Observation and modeling of high-7Be events in Northern Europe associated with the instability of the Arctic polar vortex in early 2003 - Brattich, Erika; Liu, Hongyu; Zhang, Bo; Hernández-Ceballos, Miguel Angel; Paatero, Jussi; Sarvan, Darko; Djurdjevic, Vladimir; Tositti, Laura; Ajtić, Jelena (Zenodo, 2020)
Data repository for paper: "Observation and modeling of high-7Be events in Northern Europe associated with the instability of the Arctic polar vortex in early 2003" Erika Brattich; Hongyu Liu; Bo Zhang; Miguel Angel Hernandez-Ceballos; Jussi Paatero; Darko Sarvan; Vladimir Djurdjevic; Laura Tositti; Jelena Ajtić, submitted to Atmospheric Chemistry and Physics, October 2020 Created by Erika Brattich (erika.brattich@unibo.it), October 2020 -> Data - Pb210_2sites.csv contains daily 210Pb observations at Helsinki and Sodankyla in the period January-March 2003. Dates are in "m/d/yyyy" format and 210Pb measurements are in µBq/m³. Please refer to Mattson et al. (1996) for details. -> Model output - trac_avg.merra2_2x25_RnPbBe.200301-200303-monthly-means.bpch.gz: contains model output of monthly mean 210Pb and 7Be concentrations for January, February, and March 2003. - ts_1h.200301.bpch.tar: hourly model output for January 2003 - ts_1h.200302.bpch.tar: hourly model output for February 2003 - ts_1h.200303.bpch.tar: hourly model output for March 2003 - diaginfo.dat, tracerinfo.dat: information data files needed for the GAMAP package (in IDL) used to read and process the model output. GAMAP is publicly available at: http://acmg.seas.harvard.edu/gamap/ References: Mattsson, R., Paatero, J., and Hatakka, J.: Automatic Alpha/Beta Analyser for Air Filter Samples - Absolute Determination of Radon Progeny by Pseudo-coincidence Techniques, Radiat. Prot. Dosim., 63, 133-139, doi:10.1093/oxfordjournals.rpd.a031520, 1996.